Elastic properties of silicon nitride ceramics reinforced with graphene nanofillers. (15th December 2015) - Seiner, Hanuš; Ramirez, Cristina; Koller, Martin; Sedlák, Petr; Landa, Michal; Miranzo, Pilar; Belmonte, Manuel; Osendi, Maria Isabel
Abstract: Elastic constants of silicon nitride composites with variable content (3–18 wt.%) of two kinds of graphene fillers (nanoplatelets and reduced graphene oxide sheets) are determined using resonant ultrasound spectroscopy. The corresponding Young's modulus ( E ), shear modulus ( G ) and Poisson's ratio (ν) are calculated for each material. Composites show a noticeable anisotropy that grows stronger with the graphene filler content, owing to the preferential alignment of the graphene layers and to their own anisotropy as well. E and G monotonically decrease with the filler concentration for both types of fillers, showing a maximum decrease in E of 75% along the direction perpendicular to the graphene plane for the composite with the highest filler content (Si3 N4 –18 wt.% GNP) and a reduction in G of 63% for shear along the graphene plane for the same composite. Influence on the fracture pattern of the composites is also addressed. Graphical abstract: Highlights: Elastic modulus ( E ) and shear modulus ( G ) decrease steadily with the graphene filler content. The decrease rate for both E and G depends on the exfoliation degree of the graphene filler. E, G and Poisson coefficient vary with the measurement direction. Shearability of the composites decreases compared to the monolithic material.